Students remain on campus during MCO - Mohamad Hakimi, Kamarudin (2020)
The Movement Control Order (MCO) until 14 April 2020 certainly provides the experience that will be remembered for the students of Universiti Malaysia Pahang (UMP), especially those who remain on the campus.